Cloning of a novel xylanase gene from a newly isolated Fusarium sp. Q7-31 and its expression in Escherichia coli - Xie,Zhan-Ling (2012)
A strain of Q7-31 was isolated from Qinghai-Tibet Plateau and was identified as Fusarium sp. based on its morphological characteristics and ITS rDNA gene sequence analysis. It has the highest capacity of degrading cell wall activity compared with other 11 strains. To do research on its xylanase activity of Fusarium sp. Q7-31 while the degrading the rice cell walls, the complete gene xyn8 that encodes endo-1, 4-β-xylanase secreted by Fusarium sp. Q7-31 was cloned and sequenced. The coding region of the gene is separated by two introns of 56bp and 55bp. It encodes 230 amino acid residues of a protein with a calculated molecular weight of 25.7 kDa. The animo acids sequence of xyn8 gene has higher similarity with those of family 11 of glycosyl hydrolases reported from other microorganisms. The nature peptide encodeing cDNA was subcloned into pGEX5x-1 expression vector. The recombinant plasmid was expressed in Escherichia coli BL21-CodonPlus (DE3)-RIL, and xylanase activity was measured. The expression fusion protein was identified by SDS-PAGE and Western blotting, a new specific band of about 52kDa was identified when induced by IPTG. Enzyme activity assay verified the recombinants proteins as a xylanase. A maxium activity of 2.34U/ mg, the xylanase had optimal activity at pH 6.0 and temperature 40ºC .